The clinical relevance of attentional bias in substance use disorders. (13th May 2013) - Field, Matt; Marhe, Reshmi; Franken, Ingmar H. A.
Abstract : Individuals with substance use disorders typically show an "attentional bias" for substance-related cues: Those cues are able to grab and hold the attention, in preference to other cues in the environment. We discuss the theoretical context for this work before reviewing the measurement of attentional bias, and its relationship to motivational state and relapse to substance use after a period of abstinence. Finally, we discuss the implications of this research for the treatment of substance use disorders. We conclude that attentional bias is associated with subjective craving, and that moment-by-moment fluctuations in attentional bias may precede relapse to substance use. The evidence regarding the predictive relationship between attentional bias assessed in treatment contexts and subsequent relapse is inconsistent. Furthermore, there is currently insufficient evidence to endorse attentional bias modification as a treatment for substance use disorders. Clinical implications and suggestions for future research are highlighted.